2010
DOI: 10.1002/jbm.b.31604
|View full text |Cite
|
Sign up to set email alerts
|

Potential for adhesive wear in friction couples of UHMWPE running against oxidized zirconium, titanium nitride coatings, and cobalt‐chromium alloys

Abstract: The classical wear mechanisms abrasion, fatigue, and adhesion are the most frequent causes of surface changes of ultra high molecular weight polyethylene (UHMWPE) in artificial joints. The counterpart material has a strong influence on the wear and friction behavior of artificial joints due to its abrasive properties and adhesive interaction with UHMWPE. The formation of a transfer layer on the counterpart in UHMWPE bearing systems is often described as being a clear indication of strong adhesive forces. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
0
23
0
1
Order By: Relevance
“…This film is ascribed to the intimate contact of the UHMWPE with the counterpart. The adhesive interaction between the bearing-materials can be quite high as proven by the occurrence of the transfer layer to the CoCrMo wheels [46] and the ordered crystalline structure within the polymer is destroyed. Underneath the film, a strong microfibrillar orientation was observed, shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This film is ascribed to the intimate contact of the UHMWPE with the counterpart. The adhesive interaction between the bearing-materials can be quite high as proven by the occurrence of the transfer layer to the CoCrMo wheels [46] and the ordered crystalline structure within the polymer is destroyed. Underneath the film, a strong microfibrillar orientation was observed, shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by other investigators, the presence of serum proteins initially serves to reduce adhesive wear; but upon their precipitation, adhesion increases [118]. Furthermore, it has been demonstrated that CoCr has a propensity for greater polyethylene adhesive wear than nitride-based materials [127]. Figure 3 presents comparative PE and XLPE wear data for gamma irradiated UHMWPE liners articulating against CoCr, ZrO 2 , Al 2 O 3 , and Si 3 N 4 femoral heads.…”
Section: Swm Ceramic-on-polyethylene Hip Simulator Studymentioning
confidence: 79%
“…5,6,9,27,28 Previously, cobaltchrome has been reported to have increased adhesive wear compared with oxidized zirconium on ultra-high molecular weight polyethylene. 17 More recently, cobalt-chrome has demonstrated reduced wear rates using this bearing surface, and highly crosslinked polyethylene has been recommended for younger patients undergoing total hip arthroplasty. [29][30][31][32] Our study demonstrates that excellent clinical outcomes are achievable with cobalt-chrome and oxidized zirconium femoral head articulations on a highly crosslinked polyethylene liner.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Tribiological testing has shown that oxidized zirconium has better wettability and less surface adhesion on polyethylene than cobalt-chrome. 17 Although the advantages and disadvantages of these bearing surface couples are well described, few studies have directly compared the bearing surface couples with respect to implant survivorship and clinical outcomes. Therefore, the purpose of this study was to directly compare age-, sexand body mass index (BMI)-matched cohorts of patients who received cobalt-chrome or oxidized zirconium on highly crosslinked polyethylene.…”
mentioning
confidence: 99%